2008
DOI: 10.1071/ar07163
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of grain yield conditioned on its component traits in rice (Oryza sativa L.)

Abstract: Grain yield (GY) of rice is a complex trait consisting of several yield components. It is of great importance to reveal the genetic relationships between GY and its yield components at the QTL (quantitative trait loci) level for multi-trait improvement in rice. In the present study, GY per plant in rice and its 3 yield component traits, panicle number per plant (PN), grain number per panicle (GN), and 1000-grain weight (GW), were investigated using a doubled-haploid population derived from a cross of an indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 36 publications
1
26
0
1
Order By: Relevance
“…The remaining variation excluding the contributions of causal traits is defined as conditional variation. This method is also used to analyze the influence of different agro-technologies or agronomic practices on crop growth and development to discover QTLs specifically expressed in stress environments (Jiang et al 2008;Zhang et al 2014), to identify QTLs expressed at certain developmental stages of plants (Zhu 1995;Atchley and Zhu 1997;Yan et al 1998;Cao et al 2001), or to analyze contributions of component traits to a complex trait (Guo et al 2005;Liu et al 2008;Cui et al 2011). QTL analysis of conventional P-deficient tolerance is generally aimed at analysing the expression of phenotypic traits at different P levels (Guo et al 2012;Su et al 2006;Cao et al 2001).…”
Section: Conditional Qtl and Unconditional Qtlmentioning
confidence: 99%
“…The remaining variation excluding the contributions of causal traits is defined as conditional variation. This method is also used to analyze the influence of different agro-technologies or agronomic practices on crop growth and development to discover QTLs specifically expressed in stress environments (Jiang et al 2008;Zhang et al 2014), to identify QTLs expressed at certain developmental stages of plants (Zhu 1995;Atchley and Zhu 1997;Yan et al 1998;Cao et al 2001), or to analyze contributions of component traits to a complex trait (Guo et al 2005;Liu et al 2008;Cui et al 2011). QTL analysis of conventional P-deficient tolerance is generally aimed at analysing the expression of phenotypic traits at different P levels (Guo et al 2012;Su et al 2006;Cao et al 2001).…”
Section: Conditional Qtl and Unconditional Qtlmentioning
confidence: 99%
“…More recently, a method for multivariable conditional analysis was proposed for analyzing the contributions of individual component traits to a complex trait (Wen and Zhu, 2005). By combining the conditional genetic analysis method with QTL mapping (unconditional QTL analysis), the method was extended to map conditional QTL for the molecular dissection of complex traits (Guo et al, 2005;Zhao et al, 2006;Liu et al, 2008;Cui et al, 2011). Therefore, conditional QTL mapping analysis is an efficient tool for determining relationships between complex traits and their components.…”
Section: Qtl Analysis: Corroborations and New Findingsmentioning
confidence: 99%
“…This method could be used to determine genetic interrelationships between traits at the level of individual QTL, and to find additional QTL that are undetectable with unconditional mapping (Li et al, 2008). This method has been successfully used to analyze QTL by Guo et al (2005), Zhao et al (2006), Liu et al (2008), andCui et al (2011).…”
Section: Introductionmentioning
confidence: 99%
“…Such an approach can be used to estimate the genetic contribution of one component trait (cause-trait) to the resultant trait of interest. For example, Guo et al [65] studied rice yield and its component traits using this kind of approach and a similar study has been reported by Liu et al [66]. Zhao et al [67] analyzed the relationship between oil content in rapeseed with protein content and other traits related to plant development.…”
Section: Qtl Dissection Of Genetic Correlation Between Traitsmentioning
confidence: 99%